Abundance of megalin and Dab2 is reduced in syncytiotrophoblast during placental malaria, which may contribute to low birth weight - Lybbert, Jared; Gullingsrud, Justin; Chesnokov, Olga; Turyakira, Eleanor; Dhorda, Mehul; Guerin, Philippe J.; Piola, Patrice; Muehlenbachs, Atis; Oleinikov, Andrew V. (Scientific reports, 2016)
Placental malaria caused by Plasmodium falciparum contributes to ~200,000 child deaths annually, mainly due to low birth weight (LBW). Parasitized erythrocyte sequestration and consequent inflammation in the placenta are common attributes of placental malaria. The precise molecular details of placental changes leading to LBW are still poorly understood. We hypothesized that placental malaria may disturb maternofetal exchange of vitamins, lipids, and hormones mediated by the multiligand (n ~ 50) scavenging/signaling receptor megalin, which is abundantly expressed in placenta but was not previously analyzed in pregnancy outcomes. We studied abundance of megalin and its intracellular adaptor protein Dab2 by immunofluorescence microscopy in placental biopsies from Ugandan women with (n = 8) and without (n = 20) active placental malaria. We found that: (a) abundances of both megalin (p = 0.01) and Dab2 (p = 0.006) were significantly reduced in brush border of syncytiotrophoblast of infected placentas; (b) amounts of megalin and Dab2 were strongly correlated (Spearman’s r = 0.53, p = 0.003); (c) abundances of megalin and Dab2 (p = 0.046) were reduced in infected placentas from women with LBW deliveries. This study provides first evidence that placental malaria infection is associated with reduced abundance of megalin transport/signaling system and indicate that these changes may contribute to the pathology of LBW.
Keywords: megalin; placental malaria; low birth weight